Prevalence, abundance and intensity of eggs and oocysts of gastrointestinal parasites in the opossum Didelphis virginiana Kerr, 1792 in Yucatan, Mexico - Aragón-Pech R. A.; Ruiz-Piña H. A.; Rodríguez-Vivas R. I.; Cuxim-Koyoc A. D.; Reyes-Novelo E. (Helminthologia, 2018)
Virginia opossum, Didelphis virginiana, is a synanthropic mammal associated with peridomestic areas of Yucatán, However, little is known about the gastrointestinal parasite infections of this species. The infection prevalence, mean abundance and mean intensity of eggs and oocysts of gastrointestinal parasites, in opossums captured in the peridomestic areas were estimated in six rural localities of Yucatán, Mexico. Eighty-four faecal samples were processed by flotation technique. McMaster test was used to estimate the number of helminth eggs and protozoa oocysts per gram of feces. Seven genera of gastrointestinal parasites were identified, and then infection prevalence was estimated as follows: Protozoa Eimeria sp. (51.9 %) and Sarcocystis sp. (1 %); nematodes Ancylostoma sp. (80.56 %), Cruzia sp. (62.04 %), Trichuris sp. (60.19 %), Capillaria sp. (29.63 %), Turgida sp. (23.15 %), Toxocara sp. (11.11 %), and Ascaris sp. (1.85 %); and one acanthocephalan: Oligacanthorhynchus sp. (14.81 %). This is the first study on the diversity of gastrointestinal parasites in Virginia opossums, and first evidence about the potential role of opossums in the transmission of zoonotic gastrointestinal parasites in peridomestic areas of Yucatán, Mexico.